论新加坡外籍体力劳动工作者称谓的变化及其社会属性 ：从“苦力”、“劳工”到“客工” = The transformation of terms for Singapore's foreign manual labour workers and its social qualities : from "Coolie", "Labour" to "Guest Worker" - 曾钰娟 Chang, Yu Juan (2015)
在新加坡多元文化的社会语境中，各种社会、政治与经济因素之间相互影响、相互渗透，从而产生出新加坡独特词汇。“客工”（guest worker）就是其中独特词汇，是新加坡自开垦以来经历了无数的社会演变所构成的词语。“客工”指的是外籍体力劳动工作者，是新加坡对他们的一种表示尊敬的礼貌称谓。他们因为促进新加坡经济，构成新加坡重要和备受重视的人群。本文通过挖掘词语背后所产生的意义来探讨该词所发挥的功能与价值，来了解不同阶段中的社会意识及价值取向。本文也会采取历时视角，分析“客工”的前身，“苦力”和“劳工”，是如何在历史演变的过程中间接被淘汰，并且探讨“客工”在定型过程中如何成为反映新加坡社会现象的特有词汇。 In Singapore's multicultural context, the government, social and economic factors are interlinked, causing the rise of Singapore specific Chinese vocabulary. An example of such a Chinese vocabulary would be the word, "Ke Gong", which means "guest worker". It is a respectful term for foreign manual labour workers working in Singapore because these workers are highly in demand and they contribute greatly to the Singapore's economy. Thus, they are favored by the Singapore government and are being treated with respect. Therefore, through discovering the deeper meaning of the term, it will aid us to better understand how its evolving functions can help in our understanding of the social phenomenon and values during different phases in the development of the society. By examining Singapore's history, this thesis will analyze why the words used before "Ke Gong"---"Ku Li"(coolie) and "Lao Gong" (labour), are being eliminated as the society progress and develops. Lastly, the paper will also investigate how the evolvement of "Ke Gong" eventually became a vocabulary that reflects the specific social phenomenon in the Singapore society.